Gravity Interpretation of Mud Volcano based on Satellite Data (Study Case Kuwu and Cangkring Mud Volcano) - Rina Dwi Indriana; Mariyanto Mariyanto; Eleonora Agustin; Mimin Iryanti; Cahyo Aji Hapsoro; Sorja Koesuma; Abdul Latif Ashadi (Department of Physics, Sebelas Maret University, 2024)
A mud volcano is one type of mountain in the world. Mud volcano has specific characteristics. In Java, several mud volcanoes spread from west to east of Java. Bledug Kuwu and Bledug Cangkring are mud volcanoes in Central Java. Research on the Bledug Kuwu and Cangkring mud volcanoes systems was not done. In this preliminary study, the gravitational field analysis of the Kuwu-Cangkring mud volcano system was done by using GGmPlus satellite data with a 220 m grid and elevation data using ERTM. Free air anomaly data processing obtained a complete Bouguer anomaly value of 23 to 34 mGal. The separation process of anomalies using the upward continuation method produces a local of -0.5 to 0.5 mGal and a regional of 23 mGal to 34 mGal. The local anomaly value of Bledug Kuwu was -0.275 to - 0.05 mGal and Bledug Cangkring-0.125 to 0.1 mGal. The local anomaly around Bledug Cangkring is higher than Bledug Kuwu, indicating a lower density beneath Bledug Kuwu than in Cangkring.